Wishing Upon the Same Stars - Feldman, Jacquetta Nammar (New York : Harper, an imprint of HarperCollinsPublishers, 2022)
Twelve-year-old Yasmeen Khoury is unhappy that her family has moved from Detroit to San Antonio, Texas, leaving her friends and Arab Christian community behind; from the very first day at school Yasmeen feels completely isolated and out of place, but she slowly makes friends with a Mexican boy, Carlos, and her Jewish neighbor, Ayelet Cohen, although she feels like she has to hide these friendships, especially from her Palestinian father, a native of Jerusalem--more than anything Yasmeen just wants to be American but it seems like she can not escape the ethnic tensions that swirl around her.
Keywords: Arab Americans -- Juvenile fiction; Moving, Household -- Juvenile fiction; Ethnic attitudes -- Juvenile fiction. -- Texas; Ethnic relations -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Families -- Juvenile fiction. -- Texas; Friendship -- Juvenile fiction; Arab Americans -- Fiction; Moving, Household -- Fiction; Ethnic relations -- Fiction; Fathers and daughters -- Fiction; Family life -- Fiction. -- Texas; Friendship -- Fiction; San Antonio (Tex.) -- Juvenile fiction; San Antonio (Tex.) -- Fiction; Juvenile fiction